2021
DOI: 10.24235/sc.educatia.v10i1.8486
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Science Learning Research Skills: A Meta-Analysis Study

Abstract: Research skills are our ability to find and answer a question or solve a problem. This study aimed to identify methods in the science learning of research skills. Meta-analysis study used PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) method. The stages of the research method include: determining criteria and literature search techniques, conducting literature analysis, coding, and data analysis. Jeffreys's Amazing Statistics Program (JASP) version 0.14.1 was used as a data analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(42 reference statements)
0
2
0
1
Order By: Relevance
“…These variables are guided inquiry learning models, inquiry, PBL, PjBL and learning cycles, as well as learning media variables and modules and worksheets. In addition, Aripin et al (2021) found that learning through inquiry had a moderate effect on students' science learning skills (p=.63)…”
Section: Discussionmentioning
confidence: 99%
“…These variables are guided inquiry learning models, inquiry, PBL, PjBL and learning cycles, as well as learning media variables and modules and worksheets. In addition, Aripin et al (2021) found that learning through inquiry had a moderate effect on students' science learning skills (p=.63)…”
Section: Discussionmentioning
confidence: 99%
“…Hadirnya CS dalam dunia pendidikan mendorong para peserta untuk lebih update dengan perkembangan teknologi. Hal tersebut karena salah satu ciri CS yaitu adanya sharing knowledge pada dunia digital (Aripin, I., Hidayat, T., & Rustaman, 2020;Aripin, I., Hidayat, T., Rustaman, N., & Riandi, 2021;Aripin, 2022;. Citizen science tidak hanya membantu pengumpul data dalam ilmu pengetahuan namun juga sebagai alat pendidikan inovatif (Schneiderhan & Bogner, 2020).…”
Section: B Inovasi Citizen Science Dalam Pendidikanunclassified
“…Efforts to integrate CS in education have also been developed in Indonesia, one of which is at the University of Education Indonesia with the pioneer Prof. Topik Hidayat, Ph.D from the Department of Biology Education. Research and publications on the implementation of CS education in Indonesia have also been conducted by Aripin, Damayanti, and Faizah et al who developed CS programs in higher and secondary education in Indonesia [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…OCS activities are very appropriate in Indonesia, because Indonesia is the second largest megabiodiversity country in the world. The limited number of scientists and unavailability of qualified biodiversity data base 14 so, CS activities can be an alternative solution for the collection, identification and publication of Indonesian biodiversity data 3 . To be able to contribute to the collection of Indonesian biodiversity data, the community needs to develop species identification (classification) skills.…”
Section: Introductionmentioning
confidence: 99%